Beethoven : a life - Caeyers, Jan, 1953- (University of California Press, 2020)
This new biography of Ludwig van Beethoven offers connoisseurs and newcomers alike an unparalleled story of the composer's life and works, written by a renowned conductor and scholar of Beethoven's music. With unprecedented access to the archives at the Beethoven House in Bonn, Jan Caeyers expertly weaves together a deeply human and complex picture of Beethoven-his troubled youth, his unpredictable mood swings, his desires, relationships, and conflicts with family and friends, the mysteries surrounding his affair with the 'immortal beloved,' and the dramatic tale of his deafness. Caeyers also offers new insights into Beethoven's music, showing how it transformed from the work of a skilled craftsman to that of a consummate artist. Demonstrating an impressive command of the vast scholarship on this iconic composer, Caeyers brings Beethoven's world alive with elegant prose, memorable musical descriptions, and a vivid depiction of Bonn and Vienna, where Beethoven produced and performed his works. Caeyers explores how Beethoven's career was impacted by the historical and philosophical shifts taking place in the music world and how, in turn, his trajectory changed the music industry. Equal parts an absorbing cultural history and a lively biography, Beethoven, A Life reveals a complex portrait of the musical genius that defined a style of music and went on to become one of the great pillars of Western art music.